2004
DOI: 10.1002/masy.200450221
|View full text |Cite
|
Sign up to set email alerts
|

Achieving high conversions in nitroxide‐mediated living styrene miniemulsion polymerization

Abstract: Nitroxide‐mediated living radical polymerizations of styrene were run in miniemulsion. Using a modified miniemulsion process that does not require the use of a volatile costabilizer, near complete conversions could be achieved in 2‐3 hours while preserving narrow molecular weight distributions and a high degree of chain livingness. Increased rates and final conversions were achieved by semi‐batch addition of the nitroxide scavenger ascorbic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…The STY‐1 reaction process was repeated in this reaction, except 1.8 g ascorbic acid was added to the STY‐1 formulation as a reaction accelerant to increase reaction rate and conversion 39. The ascorbic acid was mixed into the miniemulsion mixture after latex dispersion in the Niro Soavi homogenizer and 10 min before the latex was charged into the storage cylinders in the apparatus.…”
Section: Experimental Partmentioning
confidence: 99%
“…The STY‐1 reaction process was repeated in this reaction, except 1.8 g ascorbic acid was added to the STY‐1 formulation as a reaction accelerant to increase reaction rate and conversion 39. The ascorbic acid was mixed into the miniemulsion mixture after latex dispersion in the Niro Soavi homogenizer and 10 min before the latex was charged into the storage cylinders in the apparatus.…”
Section: Experimental Partmentioning
confidence: 99%
“…In most cases, S/TEMPO miniemulsion polymerizations using macroinitiator (polystyrene (PS)-TEMPO), [21,22] benzoyl peroxide/ TEMPO [23,24] or potassium persulfate/TEMPO [24][25][26][27] give R p values very similar to those in bulk. [28] Cunningham and coworkers [29,30] reported a strong dependence of R p in S/PS-TEMPO miniemulsion on the amount of the surfactant sodium dodecylbenzenesulfonate (SDBS) (the particle size distributions were ''nearly identical'' with a ''mean diameter'' of 150 nm), and speculated that SDBS or SDBS impurities consume nitroxide, thus resulting in an increase in R p . [29] Pan et al [31] reported that in the TEMPO-mediated thermal miniemulsion polymerization of S at 125 8C, the initial R p was approx.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the disadvantage of increasing the rate (greater termination rates) is partially or wholly offset by reduced disproportionation rates. We have not optimized the initiator addition process; it may in fact be possible to achieve higher livingness with the modified recipe, as has been found in mini‐emulsion SFRP 21…”
Section: Resultsmentioning
confidence: 99%